MOTIF PERBURUAN TERHADAP HARIMAU SUMATERA PADA KAWASAN TAMAN NASIONAL BUKIT TIGA PULUH KABUPATEN INDRAGIRI HULU - Irawan, Refi Elky; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This thesis is submitted in order to qualify holds a Bachelor of Sociology . With the title " Against Poaching Sumatran Tiger Motif In the Park Hill area Thirty Indragiri Hulu '' . The problem addressed in this paper is to describe the motive hunting of tigers in the Park Hill neighborhood Thirty Indragiri Hulu . The subjects in this study were people who know people who hunt tigers and tiger hunting in the village suamtera Sanglap District of Batang Cenaku . The technique of determining the number of informants in Purposived do with technique , which is purposive sampling , where people are used as research subjects are people who know about the existence of poaching of tigers and tiger hunting community in the village of Batang Cenaku Sanglap District of Indragiri Hulu ( Riau ) . The method used is qualitative methods , data collection techniques used in this study are : observation , interviews independently . The theory used for this research problem is the theory of Max Weber's theory of social action that is particularly instrumental rationality of action ( zweckrationalitas ) . Results of research conducted in general the writer can say that the motive hunting of tigers in the Park Hill neighborhood of Thirty is hunting on the basis of economic factors ( Money ) , factor conflicts between humans and tigers , lack of participation of local people in forest preserve the and wildlife therein , and the existence of law is deemed not too plays an important role in preventing and stopping Sumatran tiger poaching and trade . The hunt is often the case raises a different view on the local community jhususnya people living around the area of the Park Hill neighborhood Thirty Indragiri Hulu .